2018
DOI: 10.9734/mrji/2018/40074
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Staphylococcus aureus Isolated from Bulk Tank Milk Dairy Cow Farms in West Bank-Palestine

Abstract: This work was carried out in collaboration between both authors. Author GA designed the study, wrote the protocol and the first draft of the manuscript and managed the literature searches. Author HI performed the sample collection and analysis of these samples. Both authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Moreover, the obtained result was higher than the previous finding confirmed in the previous study in Benha Province, Dakahlia Province, and West Bank-Palestine. In these studies, the authors confirmed the presence of S. aureus in 90.4%, 81.3%, and 68.4% of the examined milk samples, respectively [30][31][32]. This high incidence of S. aureus may be attributed to several factors: (1) Its ability to be hidden inside the udder especially with poor hygienic measures before and after milking; (2) the neglected periodical cleaning; (3) the disinfection of milking pens, milking machine, and/or millker's hands which act as a potential vehicle that can carry the infection from animal to another; and (4) the neglected periodical milk examination using direct and indirect methods that can detect any increase in the SCC that acts as an indicator for subclinical mastitis.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, the obtained result was higher than the previous finding confirmed in the previous study in Benha Province, Dakahlia Province, and West Bank-Palestine. In these studies, the authors confirmed the presence of S. aureus in 90.4%, 81.3%, and 68.4% of the examined milk samples, respectively [30][31][32]. This high incidence of S. aureus may be attributed to several factors: (1) Its ability to be hidden inside the udder especially with poor hygienic measures before and after milking; (2) the neglected periodical cleaning; (3) the disinfection of milking pens, milking machine, and/or millker's hands which act as a potential vehicle that can carry the infection from animal to another; and (4) the neglected periodical milk examination using direct and indirect methods that can detect any increase in the SCC that acts as an indicator for subclinical mastitis.…”
Section: Discussionmentioning
confidence: 74%
“…The clusters of the fingerprints in the constructed dendrogram were described at a 96% similarity level. The number of different bands in each fingerprint was considered for comparison between S. Typhimurium strains as previously described Adwan and Haya, 2018), based on the following criteria: identical clones (no different bands), "closely related clones" (have 1 different band),"possibility different clones" (have two different bands), "different clones" (have three or more different bands).…”
Section: Molecular Typing By Eric-pcr and Box-air-pcrmentioning
confidence: 99%